Bước đầu ứng dụng xạ trị đích trong mổ (intrabeam) điều trị ung thư vú - Tùng, Nguyễn Đình; Hiệp, Phạm Như; Bảo, Đặng Như; Dũng, Nguyễn Việt; Phúc, Nguyễn Văn; Hùng, Lê Trọng; Tuấn, Nguyễn Hữu Minh; Dũng, Nguyễn Cao (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.